Mechanisms of zolpidem‐induced long QT syndrome: acute inhibition of recombinant hERG K+ channels and action potential prolongation in human cardiomyocytes derived from induced pluripotent stem cells. (20th February 2013) - Jehle, J; Ficker, E; Wan, X; Deschenes, I; Kisselbach, J; Wiedmann, F; Staudacher, I; Schmidt, C; Schweizer, PA; Becker, R; Katus, HA; Thomas, D
<x xml:space="preserve">Abstract</x> Background and Purpose Zolpidem, a short‐acting hypnotic drug prescribed to treat insomnia, has been clinically associated with acquired long QT syndrome (LQTS) and torsade de pointes (TdP) tachyarrhythmia. LQTS is primarily attributed to reduction of cardiac human ether‐a‐go‐go‐related gene (hERG)/IKr currents. We hypothesized that zolpidem prolongs the cardiac action potential through inhibition of hERG K+ channels. Experimental Approach Two‐electrode voltage clamp and whole‐cell patch clamp electrophysiology was used to record hERG currents from Xenopus oocytes and from HEK 293 cells. In addition, hERG protein trafficking was evaluated in HEK 293 cells by Western blot analysis, and action potential duration (APD) was assessed in human‐induced pluripotent stem cell (hiPSC)‐derived cardiomyocytes. Key Results Zolpidem caused acute hERG channel blockade in oocytes (IC50 = 61.5 μM) and in HEK 293 cells (IC50 = 65.5 μM). Mutation of residues Y652 and F656 attenuated hERG inhibition, suggesting drug binding to a receptor site inside the channel pore. Channels were blocked in open and inactivated states in a voltage‐ and frequency‐independent manner. Zolpidem accelerated hERG channel inactivation but did not affect I–V relationships of steady‐state activation and inactivation. In contrast to the majority of hERG inhibitors, hERG cell surface trafficking was not impaired by zolpidem. Finally, acute zolpidem exposure resulted in APD prolongation in hiPSC‐derived cardiomyocytes. Conclusions and Implications Zolpidem inhibits cardiac hERG K+ channels. Despite a relatively low affinity of zolpidem to hERG channels, APD prolongation may lead to acquired LQTS and TdP in cases of reduced repolarization reserve or zolpidem overdose.